The biological thinking between Searle and Garson - فرحة محمد; ملاح هبه (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
Can Garson rival Searle in his biological philosophy? This is what we will focus on in research by making a comparison between Searle and Garson regarding their respective views on mind and biological thinking. And what branches off from it from other issues such as artificial intelligence and natural selection. In the beginning of the research, we shall try to present a philosophical conception of the biological mind. Free will will also achieve an important place between determinism and intentionality. As two primary sources of scientific and philosophical knowledge that complement one another. Taking into account the scientific developments taking place in the current era. Which, in turn, helped crystallize a new cogito. Perhaps it is revolutionizing the Cartesian heritage: I think so I am. So what are the characteristics of the new thinking? And what is it?